Micro-PIXE investigation of bean seeds to assist micronutrient biofortification - Cvitanich, C; Przybylowicz, WJ; Mesjasz-Przybylowicz, J; Blair, Matthew W.; Astudillo, Carolina; Orlowska, E; Jurkiewicz, AM; Jensen, E; Stougaard, J (Elsevier, 2011)
This study compares the distribution and concentrations of micro- and macronutrients in different bean cultivars with the aim of optimizing the biofortification, a sustainable approach towards improving dietary quality. Micro-PIXE was used to reveal the distribution of Fe, Zn, Mn, Ca, P, S in seeds of common beans (Phaseolus vulgaris) and runner beans (Phaseolus coccineus). Average concentrations of elements in different tissues were obtained using ICP-AES. The highest concentrations of Zn in the studied beans were found in the embryonic axis, but an increased concentration of this element was also detected in the provascular bundles of the cotyledons. The first layer of cells surrounding provascular bundles accumulated high concentrations of Fe, while the next cell layer had an increased concentration of Mn. The analysis showed that the provascular bundles and the first cell layers surrounding them could have a significant role in the storage of important seed micronutrients Zn, Fe, and Mn. This information has important implications for molecular biology studies aimed at seed biofortification.